Isolated Current-Fed Ac to Dc with Sepic Converter for Electric Vehicle Applications - Sivakumar, S.P.; Emayavaramban, G.; Amudha, A.; Siva Ramkumar, M.; Viyathukattuva,; Divyapriya, S. (International Journal of Psychosocial Rehabilitation, 2019)
Due to increased environmental conditions, highly complicated regulations f emission, for transportation, an alternative form is identified by the use of electric vehicles. Power electronic circuits (PECs) is integral of modern electric vehicles. DC to DC converters and DC to AC inverters are in PECs. Load utility and high power electric motor are supplied by DC to AC inverter and low voltage load and low power are supplied by DC to DC converter. There are different classes of DC to DC Converters. For charging of high power electric load, there must be an increase in output. So, it uses SEPIC converter. A type of DC-DC converter corresponds to Singleended primary-inductor converter (SEPIC). In its output, it allows, electrical potential equal to, less than or greater than input voltage. Control transistor’s duty cycle controls the SEPIC output. Voltage conversion is done in SEPIC by exchanging energy between inductors and capacitors. Modification of buck-boost converter corresponds to SEPIC boost converter. Both are similar. There are few advantages of SEPIC converter. They are, non-inverted input- same polarity of input and output voltage, between output and input, energy is coupled by using a series capacitor- to a short circuit output, better response is produced, true shutdown is possible- output goes to 0V, if switch is off. In CCM operation mode, it is easy to control this converter. Duty cycle can be changed to get a output voltage is wide range as there is a same gating pulse at both switches. Recent non-coupled inductor converters are used to make a comparison with proposed converter, with respect to number of elements, diode and switches voltage stress, voltage gain. In proposed converter, with respect to output voltage, on switches, less percentage of voltage stress is produced. High voltage gain is produced by proposed converter with less number of components when compared with other converters